Contexts of reception and refugee health: Experiences of foreign-born people in the United States and Belgium - Solveig A. Cunningham; Hadewijch Vandenheede; Rebecca Jones-Antwi (Journal of Migration and Health)
Immigrants’ health may differ with the characteristics of the place they resettle. We examined eating patterns and weight status across two differing environments - Atlanta, United States and Brussels, Belgium - collecting information on diet and health from a diverse sample of 111 refugees, asylum-seekers and other migrants. Analyses used descriptive statistics, multivariate regressions, and text analysis. People who had resettled in Atlanta reported higher weight categories than those in Belgium. In both locations, the most commonly adopted items were processed foods (71 % in Atlanta, 45 % in Brussels); many also listed adopting fruits and vegetables (31 % in Atlanta, 14 % in Brussels). Thus, changes in health-related behaviors after migration included both healthy and unhealthy components of the contexts of reception. Longer time since arrival was associated with lower odds of having adopted processed foods and higher odds of having adopted fresh foods, suggesting that dietary change is nuanced with immigrants’ integration trajectories.